Stability Analysis of Cut Slope Using RMR and SMR - Tri Puji Astuti; I Gde Budi Indrawan; Didit Hadi Barianto (Applied Research on Civil Engineering and Environment (ARCEE), 2022)
The Planjan - Tepus road is built on a slightly steep karst morphology, necessitating slope excavation works. Slope stability is one of the elements to consider, particularly in slope excavation work. The excavation depth of the slopes sampled in this research is up to 48 meters. It is critical to undertake slope stability analysis quickly, precisely, and safely. For rapidly examining slopes, empirical approaches such as Rock Mass Rating (RMR) and Slope Mass Rating (SMR) can be utilized. An examination of the limit equilibrium method was performed using Rocscience Slide v.6.0 software to assure the slope stability level further. The limit equilibrium method used is Morgenstern-Price and Spencer. The value of slope stability analysis using the RMR method is 41-53, and the rock mass quality is categorized as class III (fair). The value of slope stability analysis using the SMR method 41-53, the rock mass quality is categorized as class III (normal), with slope stability in partially stable conditions. Slope stability using the limit equilibrium method produces a safety factor value of 1.670 - 1.680 for conditions without seismic loads and 1.137 - 1.154 for conditions with seismic loads. According to the findings of this analysis, the slope is in stable (safe) conditions.